1999
DOI: 10.1155/1999/935791
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Body Weight, Bone Mineral Density and Vitamin D Receptor Gene Polymorphism in Normal and Osteoporotic Women

Abstract: In an ethnically homogeneous population of women living in Tuscany, Italy, the relationships between age, body weight, bone mineral density and the vitamin D receptor (VDR) gene polymorphism were studied, with the objective of recognizing patients at risk for osteoporosis. In 275 women bone mineral density was measured by Dual Energy X-rays Absorptiometry (DEXA). In 50 of them the individual genetic pattern for VDR was evaluated by DNA extraction followed by PCR amplification of the VDR gene, and digestion wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…FN BMD was found to be decreasing continually with growing age, in both women and men even in the late decades of life [29]. The differential effects of VDR alleles on BMD among different populations could partly explain the differences between Italian and Irish studies [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…FN BMD was found to be decreasing continually with growing age, in both women and men even in the late decades of life [29]. The differential effects of VDR alleles on BMD among different populations could partly explain the differences between Italian and Irish studies [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…Although it is difficult to decipher the exact reason for the discrepancy, we could discuss some possibilities for elucidating the conflicting observations. Perhaps the different genetic backgrounds would be responsible for the inclusive results because the varied minor allele (B) distribution has been exhibited in diverse ethnicities, with the mean frequency of 16.5% in Africans (Musumeci et al, 2009;Mansour et al, 2010), 24.5% in Asians (Lim et al, 1995;Yanagi et al, 1996;Tamai et al, 1997;Mitra et al, 2006;Kanan and Mesmar, 2008), and 42.4% in Caucasians (Melhus et al, 1994;Riggs et al, 1995;Houston et al, 1996;Vandevyver et al, 1997;Gennari et al, 1998;Fountas et al, 1999;Poggi et al, 1999;Langdahl et al, 2000;Zajickova et al, 2002;Perez et al, 2008;Mencej-Bedrac et al, 2009;Musumeci et al, 2009;Seremak-Mrozikiewicz et al, 2009). Moreover, only two studies were included in this meta-analysis to investigate the relationship between the VDR BsmI polymorphism and susceptibility to osteoporosis in Africans (Musumeci et al, 2009;Mansour et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the negative studies, the most frequent ones were those performed with markers of ADRB3 (six studies) (62) (92) (93) (94) (95) (96), PPARG (seven studies) (97) (98) (99) (100) (101) (102) (103), LPL (four studies) (94) (104) (105) (106), and UCP1 (four studies) (62) (91) (94) (96). Other markers yielding negative findings were related to ADRB2 (107) (108), LEP (109) (110), LEPR (70) (110), LIPC (111), CART (112) (113), TCF1 (114) (115), TNFA (116) (117) (118), UCP2 (119), UCP3 (120), APOA4 (121), DRD2 (64), DRD4 (122), VDR (123) (124), ESR1 (123), BRS3 (125), MC3R (126), MC4R (127), APOE (128) (129), HNF4A (114), IRS1 (90) (114) (130), HNF6 (114), IGF1R (131), IGF1 (131), INSR (132), and adiponectin (133). It should be noted that the majority of the studies with positive findings also reported nonsignificant associations with other obesity‐related phenotypes and/or candidate gene markers.…”
Section: Association Studiesmentioning
confidence: 99%